PENINGKATAN KOMPETENSI DIMENSI TIGA DENGAN RESOURCE BASED LEARNING MENGGUNAKAN MINIATUR BANGUN RUANG - dkk, Nunuk Sulistyaningrum Suprapto (Universitas Islam Negeri Sunan Kudus, 2019)
THREE DIMENSIONAL COMPETENCY IMPROVEMENT WITH RESOURCE BASED LEARNING USING A GEOMETRIC MINIATURE. This study aims to improve student mathematics learning on three dimensions discussion by applying the cooperative learning models of group investigation types using resource-based learning methods with geometric miniature teaching aids. This research was conducted at SMK Negeri 1 Batealit Jepara. The method used by this research is quasi-experimental method. The subjects were 75 students of class XI AP consisting of 37 students in the experimental group and 38 students in the control group. Mathematics learning data is taken from the evaluation test results. Indicators of success are determined if the class average get improvement from pre-action, evaluation I, and evaluation II.